Developing a Mutually Cooperative Attitude and Science Process Skills Through Experiential Learning - Novitasari, Cindy; Subekti, Hasan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Experiential learning is learning that applies learning through action, learning through activities, learning through experience, and learning through discovery and exploration. Science process skills are skills that students need to have because they are closely related to intellectual skills. Gotong royong is an activity that is done together. A group does it to complete a task or work considered useful for the common interest or welfare. This study aimed to determine the effect of the experiential learning model on science process skills and students' cooperation attitudes. The research design used was one group pretest-posttest, applied in one of the junior high schools in the Sumberrejo sub-district. Data collection techniques include tests and response questionnaires. Based on the average n-gain score of all indicators, the study results obtained a score of 0.72 with a high category. The highest increase in the indicator of making conclusions was an increase in the n-gain score of 0.75. The mutual cooperation questionnaire obtained an average percentage of all indicators of 88%. The helping indicator obtained the highest percentage, with a percentage of 90%. The analysis results of the gotong royong questionnaire show an increase in all indicators, with a high average value. Empathy and human values play an important role in improving helping attitudes. Based on the analysis of this research, it can be concluded that using an experiential learning model in learning can improve students' science process skills. The experiential learning model also effectively fosters an attitude of gotong royong in students.